Licorice extract inhibits the cGAS-STING pathway and protects against non-alcoholic steatohepatitis - Luo, Wei; Xu, Guang; Song, Zheng; Mu, Wenqing; Wen, Jincai; Hui, Siwen; Zhao, Jia; Zhan, Xiaoyan; Bai, Zhaofang; Xiao, Xiaohe (Frontiers in Pharmacology, 2023)
Background: Inflammation and fibrosis are typical symptoms of nonalcoholic steatohepatitis (NASH), which is one of the most common chronic liver diseases. The cGAS-STING signaling pathway has been implicated in the progression of NASH, and targeting this pathway may represent a new therapeutic strategy.Licorice is a widely used herb with anti-inflammatory and liver-protective properties. In this study, we assessed the effect of licorice extract on the cGAS-STING pathway. Methods: Bone marrow-derived macrophages (BMDMs) were treated with licorice extract and then stimulated with HT-DNA, 2'3'-cGAMP, or other agonists to activate the cGAS-STING pathway. Quantitative real-time PCR and western blot were conducted to analyze whether licorice extract could affect the cGAS-STING pathway. Methionine and choline-deficient diet (MCD) was used to induce NASH in mice, which were treated with licorice extract (500mg/kg) by gavage and/or c-176 (15mg/kg) by intraperitoneal injection every 2 days. After 6 weeks of treatment, histological analysis of liver tissue was performed, along with measurements of plasma biochemical parameters. Results: Licorice extract inhibits cGAS-STING pathway activation. Mechanistically, it might function by inhibiting the oligomerization of STING. Treatment with licorice extract reduced inflammation and fibrosis in MCD diet-induced NASH mice models. Furthermore, we found that the therapeutic effect of combination treatment with licorice extract and C-176 (STING inhibitor) on the pathology and fibrosis of MCD diet-induced NASH models was similar to that of licorice extract or C-176 administered alone. Conclusion: Licorice extract can inhibit the cGAS-STING pathway and improve hepatic inflammation and fibrosis in NASH mice models. It strongly suggests that licorice extract may be a candidate therapeutic for NASH.